2017
DOI: 10.1111/rda.13114
|View full text |Cite
|
Sign up to set email alerts
|

Importance of oil overlay for production of porcine embryos in vitro

Abstract: Technologies to edit the zygote genome have revolutionized biomedical research not only for the creation of animal models for the study of human disease but also for the generation of functional human cells and tissues through interspecies blastocyst complementation technology. The pig is the ideal species for these purposes due to its great similarity in anatomy and physiology to humans. Emerging biotechnologies require the use of oocytes and/or embryos of good quality, which might be obtained using in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…To beware an oil overlay and avoid evaporation of medium, large volumes of medium will be usually used. Conversely, with large volumes, important compounds such as paracrine and autocrine factors for embryo interaction can be diluted (Canseco et al, 1992;Martinez et al, 2018;Nagao et al, 2008). Gasperin et al (2010) showed that an increase in the osmolality in 400 µl medium can be avoided by adding water in the central hole of a four well plate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To beware an oil overlay and avoid evaporation of medium, large volumes of medium will be usually used. Conversely, with large volumes, important compounds such as paracrine and autocrine factors for embryo interaction can be diluted (Canseco et al, 1992;Martinez et al, 2018;Nagao et al, 2008). Gasperin et al (2010) showed that an increase in the osmolality in 400 µl medium can be avoided by adding water in the central hole of a four well plate.…”
Section: Discussionmentioning
confidence: 99%
“…The presence or absence of oil per se did not alter the output of an IVP system. If oil is used, however, the type of oil (Martinez et al., 2018; Van Soom et al., 2001) and a potential treatment of the used oil (Tae et al., 2006) have an impact on embryo development and quality. Also, the batch of the oil, especially for silicon oil ((Van Soom et al., 2001); own observations) and the storage (light and temperature; (Otsuki et al., 2009)), affect the results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations